Integrated fault-tolerant control methodology for non-linear dynamical networked control systems subject to time-varying delay - Wu, Wei; Fang, Huajing (IET control theory & applications, 2014)
This study deals with the problem of designing an integrated fault-tolerant control (FTC) methodology for non-linear dynamical networked control systems subject to time-varying delay. For the convenience of residual generation, influence caused by network-induced delay is transformed into time-varying uncertainty, which facilitates further manipulation. A fault diagnosis scheme is utilised for fault detection and isolation. On the basis of the uncertainty and fault information obtained by the fault diagnosis procedure, an FTC component is developed to compensate for the effects of uncertainty and fault. In the absence of fault, a nominal controller is employed to deal with the system uncertainty. After fault detection estimator is activated, the controller is reconfigured to guarantee the boundedness of all the system signals until the fault is isolated. After the fault is isolated, the controller is reconfigured to improve the control performance by using the fault information generated by the isolation module. In addition, the stability of the proposed scheme is rigorously investigated. Finally, a simulation example is utilised to illustrate the performance of the proposed scheme.